Reconstituting empire in the decolonisation era: taxation sovereignty and the development of the British virgin islands as a dependent tax haven - Rakei, Simon (Department of Sociology, 2023)
Tax havens are denounced for eroding the sovereignty of states to tax in their jurisdictions. Using a critical interrogative lens of Empire and Imperialism, the aim of this investigation was to understand what the developmental history of the British Virgin Islands reveals about the function of tax havens in global political economy through traditions of state and taxation sovereignty. Drawing chiefly on a combination of tax, sociology and law scholarship anchored in international political economy, along with reviewing the minutes of the British Virgin Islands Legislative Council from 1950-1992, the study adopted a sociolegal perspective in exploring the relationship between tax havens, tax sovereignty and the aspirations of an equitable global tax regime. Beyond sovereign entitlement in allocating jurisdictional rights of states to tax income or capital, or a more expanded conception of tax equity through revenue sharing, the intervention of this thesis established the need to highlight the underpinnings of the international tax system by understanding the structures which maintain tax haven dependency and their development in the first instance. The basic thesis of this study is that dependency continues to the present as a function of unequal integration helping to order and maintain a hierarchical global political economy. This thesis was built on an account of post-colonial dependency through a structural lens of a reconstituting empire and neo-colonial imperialism in the development of the British Virgin Islands in two key phases. First, the political developments of the 1950 independence decade in the legislative council's relationship with sovereignty in a federated imperial structure, which then conditioned the socioeconomic development from 1960 up to 1984. Highlighting the economic apparatus of the colonial state which structurally depended on international investment through political links maintained to Britain, the second phase is demonstrated as neo-colonial imperialism and external reliance evinced through the function of the Executive Council. The thesis traced a consistent line of legislative amendments from the dawn of legislative independence providing tax incentives packages and exemptions aimed at attracting foreign capital through extensive tax holidays. This phase of neo-colonial imperialism reached its apogee in the International Business Companies Act of 1984. The parallels in the financial architecture imposed by the Foreign Commonwealth Office at the twilight of the 20th Century has striking similarities to the more recent initiatives targeted at tax havens, illustrating how the interests of metropolitan powers are maintained. Therefore, I argue and demonstrate that, the development of the British Virgin Islands as a tax haven and its integration in international political economy reveals a tradition of sovereignty in the post-colonial context which shapes neo-colonial imperialism wherein effective sovereignty remains located in the global north.